Testing and modeling blast loading of a sandwich structure cored with a bio-inspired (balanus) core. (June 2022) - Tuzgel, Firat; Akbulut, Emine Fulya; Guzel, Erkan; Yucesoy, Atacan; Sahin, Selim; Tasdemirci, Alper; Guden, Mustafa
Abstract: The blast loading response of a sandwich structure consisted of bio-inspired (balanus) cores/units was investigated experimentally and numerically. A Direct Pressure Pulse (DPP) set-up was used to impose a blast-like loading. The equivalent blast conditions corresponding to the used impact velocities were implemented in the models. A benchmark study was performed by using three different methods namely pure Lagrangian, Arbitrary Lagrangian Eulerian, and hybrid. Dynamic crushing behavior was analyzed and exhibited a higher specific energy absorption capacity than its constituents (core and shell). Among the core configurations, all-front configuration was found the most efficient configuration regarding the specific energy absorption. Highlights: The blast loading response of a sandwich structure was investigated. The bio-inspired geometry exhibits a higher specific energy absorption capacity. All-front configuration was found the most efficient configuration regarding SAE.